Interrogating Teachers’ Competencies in Teaching Social Science: The Social Realist Perspective - Karabo Molapo; Khashane Stephen Malatji1 (E-Journal of Humanities, Arts and Social Sciences)
Teachers’ competency is one of the significant skills in the teaching profession and it relies more on pedagogical and content knowledge that teachers portray when delivering a lesson. However, the competency of teachers in Social Science teaching does not match well with the seven roles of an educator. The culture of teaching Social Science in schools has however changed. Hence, the study interrogates the teacher’s competencies in Social Science teaching using the social realist perspective. The study followed a qualitative approach placed within the interpretivism paradigm where case study design was used. Purposive sampling was used to select ten Social Science teachers from secondary schools in the Capricorn District in South Africa. Individual semi-structured interviews and document analysis were used to collect data. The data was analysed through a thematic approach. From Archer’s Social Realist Theory, the concepts of Structure, Culture and Agency were used to interpret professional competencies of Social Science teachers. The study revealed that teaching skills can only be improved by frequent or continuous workshops that incorporate both pedagogical and professional competencies. The study concluded that there is a need to ground teaching pedagogy of Social Science and embed it within the seven roles of an educator. The study recommends that the social realist theoretical lenses of Structure, Culture, and Agency be embedded in teaching to regain the competency of teachers in teaching Social Science.